1998
DOI: 10.1074/jbc.273.4.2153
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Crystal Structure of a Human Tumor Necrosis Factor-α Mutant with Low Systemic Toxicity

Abstract: A human tumor necrosis factor-␣ (TNF-␣) mutant (M3S) with low systemic toxicity in vivo was designed, and its structures in two different crystal packings were determined crystallographically at 1.8 and 2.15-Å resolution, respectively, to explain altered biological activities of the mutant. M3S contains four changes: a hydrophilic substitution of L29S, two hydrophobic substitutions of S52I and Y56F, and a deletion of the Nterminal seven amino acids that is disordered in the structure of wild-type TNF-␣. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 47 publications
1
36
0
2
Order By: Relevance
“…Likewise, intrinsic conformational stability is expected to provide increased resistance to chemical and proteolytic degradation of therapeutic proteins in vivo (16) but is probably just one of several factors that influence drug bioavailability and in vivo half-life. Nonetheless, several studies have demonstrated that increasing the conformational stability of therapeutic enzymes, cytokines and antibodies can correlate to increased efficacy and/or half-life in vivo (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, intrinsic conformational stability is expected to provide increased resistance to chemical and proteolytic degradation of therapeutic proteins in vivo (16) but is probably just one of several factors that influence drug bioavailability and in vivo half-life. Nonetheless, several studies have demonstrated that increasing the conformational stability of therapeutic enzymes, cytokines and antibodies can correlate to increased efficacy and/or half-life in vivo (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce its serious systemic toxicity and enhance its in vivo stability, a great number of mutants have been constructed and evaluated for the clinical applicability (22)(23)(24). It has been found that M3S is much more resistant to the proteolysis by trypsin than wild-type TNF-␣ (wtTNF-␣) (19,25). Two cleavage sites of wtTNF-␣, Arg 6 and Arg 44 ( Fig.…”
mentioning
confidence: 99%
“…Recently, we have reported the design and X-ray structure of a human tumor necrosis factor-␣ (TNF-␣) mutant (M3S) with low systemic toxicity in vivo (18,19). The biochemical properties of TNF-␣ have been studied extensively because of its potential use as a therapeutic agent for cancer patients (20,21).…”
mentioning
confidence: 99%
“…Acute lethal toxicities of wild-type TNF-α and selected muteins in D-galactosamine-sensitized ICR mice at positions 52 and 56 on the bottom region of the TNF-α trimer. This mutein showed a high cytotoxic activity towards various human tumor cells and exhibited anticancer activities against transplanted human tumors in nude mice (16)(17)(18). The diverse activities of TNF are mediated by binding to each of the two receptors, TNF-R55 (55 kDa) and TNF-R75 (75 kDa), on the cell surface.…”
Section: Introductionmentioning
confidence: 99%